Vsegda za kadrom . Vsegda za kadrom . Always Off Screen . Всегда за кадром - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Aleksandr Kurliandskii's autobiography is presented in the form of clips from movies and cartoons. Featured in the program: Kurliandskii, Aleksandr (Writer) Автобиография Александра Курляндского представлена в форме нарезки из художественных и мультипликационных фильмов. В программе участвуют: Курляндский, Александр (Писатель)